Foamed-Metal-Based Catalytic Afterburners in Automotive Exhaust Systems; Russian Journal of Applied Chemistry; Vol. 67, iss. 2 - Pestryakov A. N. Aleksey Nikolaevich (1994, 1994)
Properties of exhaust afterburning catalysts based on porous cellular materials (foamed metals) have been investigated. Catalysts containing oxides of base metals provide a two-to-threefold reduction of CO emission. Platinum-containing foamed catalysts lower the toxicity of exhaust by 85-90%. A favorable effect is demonstrated by the combined use of afterburners and a motor oil additive based on ultradispersed copper.